A Prospective Study on Risk Factors for Acute Kidney Injury and All-Cause Mortality in Hospitalized COVID-19 Patients From Tehran (Iran) - Rostami, Zohreh; Mastrangelo, Giuseppe; Einollahi, Behzad; Nemati, Eghlim; Shafiee, Sepehr; Ebrahimi, Mehrdad; Javanbakht, Mohammad; Saadat, Seyed Hassan; Amini, Manouchehr; Einollahi, Zahra; Beyram, Bentolhoda; Cegolon, Luca (Frontiers in Immunology, 2022)
Background Several reports suggested that acute kidney injury (AKI) is a relatively common occurrence in hospitalized COVID-19 patients, but its prevalence is inconsistently reported across different populations. Moreover, it is unknown whether AKI results from a direct infection of the kidney by SARS-CoV-2 or it is a consequence of the physiologic disturbances and therapies used to treat COVID-19. We aimed to estimate the prevalence of AKI since it varies by geographical settings, time periods, and populations studied and to investigate whether clinical information and laboratory findings collected at hospital admission might influence AKI incidence (and mortality) in a particular point in time during hospitalization for COVID-19. Methods Herein we conducted a prospective longitudinal study investigating the prevalence of AKI and associated factors in 997 COVID-19 patients admitted to the Baqiyatallah general hospital of Tehran (Iran), collecting both clinical information and several dates (of: birth; hospital admission; AKI onset; ICU admission; hospital discharge; death). In order to examine how the clinical factors influenced AKI incidence and all-cause mortality during hospitalization, survival analysis using the Cox proportional-hazard models was adopted. Two separate multiple Cox regression models were fitted for each outcome (AKI and death). Results In this group of hospitalized COVID-19 patients, the prevalence of AKI was 28.5% and the mortality rate was 19.3%. AKI incidence was significantly enhanced by diabetes, hyperkalemia, higher levels of WBC count, and blood urea nitrogen (BUN). COVID-19 patients more likely to die over the course of their hospitalization were those presenting a joint association between ICU admission with either severe COVID-19 or even mild/moderate COVID-19, hypokalemia, and higher levels of BUN, WBC, and LDH measured at hospital admission. Diabetes and comorbidities did not increase the mortality risk among these hospitalized COVID-19 patients. Conclusions Since the majority of patients developed AKI after ICU referral and 40% of them were admitted to ICU within 2 days since hospital admission, these patients may have been already in critical clinical conditions at admission, despite being affected by a mild/moderate form of COVID-19, suggesting the need of early monitoring of these patients for the onset of eventual systemic complications.